Graphics calculators use in Precalculus and achievement in Calculus (1997)
Most studies on the effects of graphics calculators on students' achievement in precalculus use specially designed tests that are implemented immediately after the introduction of the technology. In many cases, the way the new technology is integrated into the curriculum is not taken into account. This study analyzed the achievement on calculus of students who took a curriculum innovation in a precalculus course that involved graphics calculators use. Even though no differences were found between the nonÐcalculators and calculators groups at the adaptation phase, significant differences were found between these two groups at the consolidation phase, and between the calculators groups of the adaptation and consolidation phases.